The problem solving ability of 7th grade students on problem based learning assisted by mathematics mobile learning application - Santoso, Fitrah adindaru; Sedjoko, Edy (Department of Mathematics, Universitas Negeri Semarang, 2019)
Developments in mobile technology and mobile phone have significantly improved. Learning using multimedia and networking becomes a mindset that must be applied. The low level of problem solving abilities of students requires educators to apply new approaches on learning. For this reason, this research aims to develop and determine the feasibility of android product based mobile learning application on Problem Based Learning and investigate individual completeness and classical completeness on students' problem solving abilities on Problem Based Learning assisted by Mathematics Mobile Learning Application. This research used the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The technique of collecting data uses tests, questionnaires, documentation, observation. The technique of analysis data uses a Likert scale, average test, and proportion test. The product of application was tested on 4 groups of respondents according to the research flow, namely material experts, media experts, teachers, and students of Junior high school 16 Semarang. The android-app products are named learning rectangle. Results 1) Based on the research that has been carried out, mobile learning applications have been developed to support mathematics learning in square and rectangular sub-material for junior high school students. This application is named Learning Rectangle which can be run on an Android smartphone. After going through the feasibility test phase, learning rectangle application is worthy of being used as a support for mathematics learning in square and rectangular sub-material for junior high school students with a percentage of eligibility of 93,68% and included in the criteria of very feasible. 2) Problem solving ability of 7th Grade Students in quadrilateral with rectangular and square sub-material in the PBL model Assisted by MMLA reached the learning completeness criteria. 3) Students' responses to the application have a positive effect on students' problem solving abilities in PBL assisted by MMLA, with a determination coefficient of 0,132 or an influence of 13,2% on students' problem solving abilities